Are novice drivers competent to take over control from level 3 automated vehicles? A comparative study with experienced drivers. (August 2021) - Chen, Facheng; Lu, Guangquan; Lin, Qingfeng; Zhai, Junda; Tan, Haitian
Highlights: This is the first paper to study the impact of manual driving experience on takeover performance in level 3 automation. The interaction effects among driving experience, takeover time budget, and secondary task were also studied. Rich manual driving experience cannot make takeover process of experienced drivers more stable under conditions of eye-off-road. Novice drivers have poor takeover stability and adaptability, but their longitudinal collision risk is not deteriorated by the lack of driving experience. Abstract: With level 3 automated vehicles poised to appear on the roads soon, takeover remains a major challenge. At present, the effect of manual driving experience on takeover performance is unknown. Therefore, a simulator study was conducted to investigate the influence of driving experience (novice and experienced) on takeover performance in different takeover time budgets (7 s and 5 s) and in combination with a visual secondary task (i.e., surrogate reference task). Data from 48 young and middle-aged participants consisting of 24 novice and 24 experienced drivers were used for this study. Researchers found that the overall stability of evasive maneuvers by novice drivers was considerably worse than that by experienced drivers. A detailed analysis showed that the influence of driving experience on takeover stability was mainly reflected in longitudinal control rather than lateral control. A significant interaction between driving experience and visual secondary task showed that the latter had a substantial impact on the takeover stability of experienced drivers but not on that of novice drivers. Researchers also found that rich manual driving experience cannot make the takeover process of experienced drivers more stable than that of novice drivers under conditions of eye-off-road. In addition, no significant difference was found between novice and experienced drivers in automation disengagement time, takeover time and minimum time to collision. Results indicate that novice drivers have poor takeover stability and weak adaptability, but their longitudinal collision risk is not deteriorated by the lack of manual driving experience.